Drug Interactions in Autoimmune Systemic Lupus Erythematosus (SLE) - Safitri, Rosyida Awalia; Sayogo, William; Muflihan, Yenni; Maela, Nurul; Setiawan, Yuni Wahyuningsih; Rahma, Sita Fauzia (PT FORMOSA CENDEKIA GLOBAL, 2024)
One of the factors that influence the success of therapy in autoimmune diseases such as SLE is the interaction of drugs with other active compounds. Several studies have stated that there are drug interactions with drugs or with other active compounds such as herbs which can support therapy or inhibit the effects of drug therapy. This review aims to investigate drug interactions in autoimmune diseases with a focus on systemic lupus erythematosus (SLE). The method used is a systematic review with literature sources in the form of international journals or research articles, and 31 articles met the inclusion criteria. There is evidence of interactions between drugs for the treatment of SLE, such as non-steroidal anti-inflammatory drugs (NSAIDs), corticosteroids, and immunosuppressants. In addition, results were obtained regarding the interaction of SLE therapy with herbal plants such as Cecendet or Physalis angulata L, horsetail, and fertilizing plants such as Manjakani, Kacip Fatimah, Chlorophyll, and Spirulina as well as interactions between drugs in both SLE therapies with other types of SLE drugs and with herbal medicine, these interactions can support or hinder the therapeutic effect of the drug